Etika Ekosentrisme Berbasis Pancasila Dalam Mewujudkan Ketahanan Pangan di Desa Bila Riase Sidenreng Rappang - Emanuel Omedetho Jermias; Abdul Rahman; Ilham Samudra Sanur (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to elaborate on the ethics of ecocentrism that are intertwined with Pancasila in the farming community in Bila Riase Village in realizing food security. This study uses a qualitative research method, where data is obtained through observation and interviews. The data is then analyzed through three stages, namely data processing, data organization, and drawing conclusions. The results of the study indicate that the values ​​of Pancasila are constructed by the farming community in Bila Riase Village through the ethics of ecocentrism that places the environment as a responsibility to be managed together in realizing sustainable food security. Food security as a mandate of Pancasila echoed by the central government is followed up by the farming community in Bila Riase Village together with village government officials to utilize the surrounding nature, especially rice fields to be managed based on the principles of mutual cooperation.